Das normas legais às normas de decisão: a inefetividade dos precedentes vinculantes do Brasil - Bonfiglio, Stefani Urnau (Universidade do Vale do Rio dos Sinos, 2020)
The jurisprudentializing phenomenon of the legal system with roman-canonical tradition has, within Brazilian reality, its own characteristics; it surpasses the constitutionally established limits and assigns binding power to the decision-making norms provided for in article 927 of the Code of Civil Procedures of March 16th, 2015. The so-called binding precedents require resignifying the constitutional principles of the functional tripartition of powers and lawfulness which, according to neoconstitutionalism, considered as a constitutional theoretical framework by the doctrine of binding precedents in(from) Brazil, would be overmatched and, consequently, legitimized the displacement of the normative source from the Law of the Legislative to that of the Judiciary. Moreover, according to the doctrine of binding precedents in(from) Brazil, positivism would likewise have been superseded by the rise of the Genoese realist decision-making and of the stare decisis, both capable of molding legal decisions through binding and the judgment of their usefulness, which is making the legal system stable and uniform, in order to attain the ideal of legal certainty, liberty, and equality through binding precedents. Therefore, this dissertation aims to determine whether allocating a binding and universalizing effect to specific legal decisions is effective, that is, whether it matches the normative mission it was intended for as per article 926 of the Code of Civil Procedures/15. Using the Hermeneutic Critique of Law as a theoretical framework, the effectiveness of assigning a binding and universalizing effect to the decisions listed in article 927 of the CCP/2015 will be questioned, taking into consideration that, even though this practice makes legal decisions stable and uniform, it does not assist in building the needed integrity and coherence between binding precedents and the decisions preceding them. Moreover, there is the questioning about binding precedents being able to cooperate, correctly and validly, for the achievement of Law, once the binding they impose is originated from functional subordination, and not from adhering to foundations predisposed to a constitutionally appropriate answer. Predominantly, when our tradition of enunciating theses tends to assign binding power to the norm that contains in itself the ultimate signification of Law and the civil procedure practice lays in the hands of the same court discretion that exempts judges of all jurisdiction degrees from abiding by the law. This empirical study followed the criteria outlined and justified in the research design, thus establishing a potentially binding “thesis” and a discussion object before the Supreme Court of Justice and the Supreme Federal Court, the theme of 11,123 legal decisions made in the period of 11 years by the Brazilian State Justice, and a representative sample of 369 legal decisions. The analysis of the latter by using 17 questions based on the assumptions of the Hermeneutic Critique of Law (HCL) and of the Constitutionally Appropriate Answer (CAA) followed the hermeneutic-phenomenological method. As an outcome, we concluded that the binding precedents in(from) Brazil are ineffective once they do not reflect the historicity (integrity and coherence) of genuine precedents, and its illegitimate binding trait is not the product of complying with the foundations of a Constitutionally Appropriate Answer, but rather of a hierarchical–functional subordination.
Keywords: Precedentes vinculantes; Legalidade; Realismo Genovês; CHD; RAC; Binding precedents; Lawfulness; Genoese Realism; HCL; CAA; ACCNPQ::Ciências Sociais Aplicadas::Direito